2015
DOI: 10.1038/mt.2015.66
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte/Macrophage-derived IGF-1 Orchestrates Murine Skeletal Muscle Regeneration and Modulates Autocrine Polarization

Abstract: Insulin-like growth factor 1 (IGF-1) is a potent enhancer of tissue regeneration, and its overexpression in muscle injury leads to hastened resolution of the inflammatory phase. Here, we show that monocytes/macrophages constitute an important initial source of IGF-1 in muscle injury, as conditional deletion of the IGF-1 gene specifically in mouse myeloid cells (ϕIGF-1 CKO) blocked the normal surge of local IGF-1 in damaged muscle and significantly compromised regeneration. In injured muscle, Ly6C+ monocytes/ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
267
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(285 citation statements)
references
References 53 publications
15
267
2
1
Order By: Relevance
“…hi macrophages fulfill the designation of restorative macrophages given their ability to produce proregenerative factors (e.g., insulin-like growth factor-1 [29]) and their contribution to muscle regeneration by acting on both myogenic (13) and fibroadipogenic (48) precursors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…hi macrophages fulfill the designation of restorative macrophages given their ability to produce proregenerative factors (e.g., insulin-like growth factor-1 [29]) and their contribution to muscle regeneration by acting on both myogenic (13) and fibroadipogenic (48) precursors.…”
Section: Discussionmentioning
confidence: 99%
“…The expression pattern of a series of molecules secreted by macrophages and involved in myogenesis (insulin-like growth factors, urokinase plasminogen activator, platelet-derived growth factor a, hepatocyte growth factor, bone morphogenetic protein 2 [24][25][26][27][28][29]) was increased with time of regeneration, and particularly in Ly6C neg macrophages (Fig. 3C).…”
Section: Comparative Analysis Of Ly6c Pos and Ly6c Neg Macrophage Submentioning
confidence: 99%
“…Knuever and colleagues have shown that myeloid cell-restricted insulin and IGF-1 receptor deficiency protects mice from skin inflammation by decreasing pro-inflammatory cytokine production from epidermal cells (Knuever et al, 2015). Monocyte and macrophage-derived IGF-1 has also been identified as a critical factor in skeletal muscle repair (Tonkin et al, 2015). Finally, anti-inflammatory macrophages also regulate the development and maintenance of IL-10 and TGF-β1 producing Treg cells, which contribute to the resolution of tissue-damaging inflammatory responses in multiple tissues (Soroosh et al, 2013).…”
Section: Protective Roles For Anti-inflammatory and Anti-fibrotic Macmentioning
confidence: 99%
“…Insulin growth factor-1 (IGF-1), which is a master regulator of myogenesis and skeletal muscle growth, is expressed mainly by macrophages during muscle regeneration and is required for their skewing in an autocrine way (324). One study reported that ROS suppression (UK-134 and a-lipoic acid) restores IGF-1 sensitivity of diabetic fibroblasts and improves their healing functions both in vitro and in vivo (37).…”
Section: A Myeloid Cellsmentioning
confidence: 99%